In-silico study of compounds of Curcuma xanthorriza against enzyme tyrosinase sac and α-MSH - Mustarichie, Resmi; Ramdhani, Danni (Asian Journal of Pharmaceutical Research and Development, 2022)
Previous report determined that curcumin, demetoxycurcumin and xanthorrhizol are an active compounds contained in Curcuma xanthorrhiza which have activity in inhibiting the tyrosinase enzyme and α-melanocyte stimulating hormone (α-MSH ) in vitro. This study aimed to determine and visualize the interaction of the three compounds with the tyrosinase enzyme and α-MSH in order to find their possibility for skin whitening. The experiment carried out using Auto Dock Vina program .The results of docking simulations showed that the three compounds can interact spontaneously with the tyrosinase enzyme and α-MSH. On the tyrosinase enzyme, xanthorrhizol interact most easily through the formation of hydrogen bonds with Asn205. On the α-MSH, demethoxycurcumin interact most easily through the formation of two hydrogen bonds with His3 and Arg5. With the inhibitory effect on the enzyme tyrosinase and α-melanocyte stimulating hormone (α-MSH) means preventing the formation of skin coloring pigment melanin, indicating that the three compounds studied can be applied as skin whitening agents.